An Integrated Depok Smart City Evaluation - Arista, Artika; Ermatita, Ermatita; Bunga Wadu, Ruth Mariana (JOIV : International Journal on Informatics Visualization, 2024)
Given the complicated pressures brought on by the fast pace of urbanization, innovative and long-lasting solutions to the issues arising from urban expansion are needed. To ensure a greater standard of life for their citizens and make sustainable growth one of their long-term goals, cities will need to make more inventive, persistent, and successful changes to their infrastructure. Nonetheless, smart cities require complex solutions to problems involving ICT, economics, government, social issues, the environment, and transportation. The sustainability of smart cities is now a topic that academics, environmental policymakers, and governmental organizations are more interested in. Depok's smart city must be evaluated to determine its capacity to fulfill the desired vision to help implement the Movement Towards 100 Smart Cities. This study offers an evaluation approach for the Depok smart city. Three indices were used to construct an integrated evaluation approach: the IMD Smart City Index 2023, The Cities of the Future Index, and the Global Power City Index. None of the indexes' results include all six of the Depok Smart City's necessary dimensions. Thus, the advice was to merge the three indices into an integrated evaluation approach for evaluating the six primary dimensions of the Depok Smart City. The results of this study also offer a sample measurement statement according to Depok Smart City. Furthermore, follow-up actions that the government or stakeholders can take to improve Depok's smart city performance include implementing the integrated matrix indicators and evaluating their validity and relevance in the real world.